Entity-elimination or threat management?: Explaining Israel’s shifting policies towards terrorist semi-states - Honig, Or Arthur (Terrorism and political violence, 2020)
Israel’s policy towards both terrorist semi-states (TSS)—Fatahland and Hamas-controlled Gaza—shows a puzzling variation over time between threat-management (i.e., deterrence and/or brute force capacity-reduction) and entity-elimination. We hold that a military-based cost-benefit analysis cannot fully account for this variation. This explanation predicts that Israel would avoid the costly and risky TSS-elimination as long as Israel can effectively manage the military danger through the much cheaper deterrence/periodical capacity reduction or when there is a high risk of not getting a much better option partly due to the danger of creating a power-vacuum into which other terrorists may reenter. Yet, some Israeli Prime Ministers pursued TSS-elimination notwithstanding the vacuum consideration and deterrence working. By adding a non-military variable—the extent to which Israel’s policy-makers believe that the TSS harms their ideologically-preferred foreign policy goals—we can better reconstruct changes in threat perception and hence better explain policy variation. The TSSs became an intolerable danger only when non-military threats were involved. Israel was willing to tolerate TSSs when the Prime Minister believed they did not pose a political/ideological threat but sought to eliminate them when he thought they did, if there seemed to be a feasible alternative.